2016
DOI: 10.4174/astr.2016.91.2.66
|View full text |Cite
|
Sign up to set email alerts
|

Does Korea's current diagnosis-related group-based reimbursement system appropriately classify appendectomy patients?

Abstract: PurposeAs several years have passed since the implementation of the Korean diagnosis-related group (DRG) payment system for appendicitis, its early outcomes should be assessed to determine if further improvements are warranted.MethodsWe retrospectively analyzed clinical data from Korean patients who underwent appendectomy, dividing the sample into 2 groups of those who received services before and after implementation of the DRG system. Based on the DRG code classification, patient data were collected includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…South Korea started to introduce national health insurance in 1977 and adopted a fee-for service (FFS) system for health care services [6]. FFS refers to a payment system that healthcare provider is paid for each service conducted, and research has indicated that FFS systems result in rapid increases in medical costs [7]. The Korean government decided to introduce a DRGs payment system to solve problems stemming from overtreatment under the FFS system.…”
Section: Introductionmentioning
confidence: 99%
“…South Korea started to introduce national health insurance in 1977 and adopted a fee-for service (FFS) system for health care services [6]. FFS refers to a payment system that healthcare provider is paid for each service conducted, and research has indicated that FFS systems result in rapid increases in medical costs [7]. The Korean government decided to introduce a DRGs payment system to solve problems stemming from overtreatment under the FFS system.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that older age and open appendectomy were associated with prolonged hospital stay, corroborating previous study results [ 28 ]. The absolute lengths of hospital stay in our results may be longer than those in other countries [ 29 ], which may be associated with the generous reimbursement policy of Korean national medical insurance system in regard to hospitalization cost [ 30 ].…”
Section: Discussionmentioning
confidence: 81%
“…Introduction of diagnosis-related group (DRG) systems where hospitals cover medical cost payments for patients undergoing appendectomy has been shown to reduce significantly the economic burden for patients in relation to medical costs nationwide [ 15 ]. Despite patients with appendectomy staying longer in hospital compared to the average length of hospital stay, their costs tend not to increase due to the DRG system [ 16 ]. However, some patients decline postoperative discharge from the hospital until complete recovery, despite lack of pain and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…patients undergoing appendectomy has been shown to reduce significantly the economic burden for patients in relation to medical costs nationwide [15]. Despite patients with appendectomy staying longer in hospital compared to the average length of hospital stay, their costs tend not to increase due to the DRG system [16].…”
Section: Introduction Of Diagnosis-related Group (Drg) Systems Where mentioning
confidence: 99%